Knowledge among Nurses Regarding Post-Partum Depression in a Tertiary Hospital Setting of Nepal (Journal of Psychiatrists' Association of Nepal, 2019)
Introduction: Postpartum depression is an important health problem which influences well-being, quality and security of life and may cause more serious problems than major depression occurring in normal life periods. It has an adverse influence on self-esteem, skills, child care, familial responsibility and roles of the mother. The aim of the study was to find out nurses’ knowledge regarding postpartum depression.Material And Method: Descriptive study design was used to find out the knowledge regarding postpartum depression among nurses. Seventy-four nurses were selected from general and critical care units of a hospital by non probability enumerative sampling technique for the study. Data was collected by pre tested self-administered semi-structured questionnaire and collected data was analyzed by descriptive statistics (frequency, percentage, mean and standard deviation) with SPSS version 20.Results: Fifty percent of respondents knew postpartum depression (PPD) is a type of mood disorder associated with childbirth. Majority of respondents knew poor marital relationship (85%), unwanted and unplanned pregnancy (83.88%), previous mental illness (78.40%) and lack of family support (66.20%) are risk factors of PPD. Regarding symptoms of PPD respondents knew low energy (78.37%), extreme sadness (68.91%), changes in sleeping and eating pattern (67.56%) and crying (66.21%). Eighty percentages of the respondents knew PPD can be identified by observation and antidepressant drug (88%) and psychotherapy (83.78%) are medical management of PPD. Majority of respondents knew nursing management of PPD are maintaining close observation of mother (93.24%), maintaining safe environment (86.48%) and family counseling (83.78%). Eighty one percentage respondents knew poor mother infant attachment is main consequence of PPD in child and poor relationship (54.05%), suicide (33.79%) and harm to baby (12%) in mother. Fifty four percentages had low knowledge regarding PPD.Conclusion: It is concluded that knowledge regarding PPD is inadequate among nurses. It is recommended that hospital management should provide in-service education to nurses to uplift their professional knowledge regarding PPD and encourage applying knowledge in practice during care of women with PPD.